Mobility of social processes as a resource of society. Correlation of the concepts of pathology, deviation, mutations - S. I. Shlyapin (Вестник университета)
The article considers the correlation of   the concepts of   pathology, deviation and mutation based on   the theoretical content from the list of   references. Deviation is   not always purely negative. We  prove this through H. Becker’s work “Outsiders”. Social groups create rules, and deviants are not able to   obey the accepted norms and become outsiders. We   have called this approach sociocul-tural. The approach described in  V.N. Zheleznyak’s monograph through the prism of   rationalistic philosophy is  more difficult to  understand and present the phenomenon of   deviation. The main idea that is   revealed in  the author’s narrative is  as follows: the classical epistemology of   rationalism is  the mind’s report on   its self-improvement. Through the socio-biological approach, deviation is   considered with the help of   the prism of   the evolutionary theory and influence of   mutations on  development. If  we study mutations of   the social life of   society, then we  can call this system a  socio-cultural mutation. The last approach was the physiological (anthropological) one. From its points of  view, it   is said about a   difference in  the origin of  the races of   people, hence the likely deviation. S.V. Savelyev in   his lecture material has considered the social evolution of   the human brain with the help of   the anthropological approach. Here we   can impose the phenomenon of   deviation on  the author’s theses, as   if describing behaviour through the anthropological differences.